2021
DOI: 10.1186/s12938-021-00895-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro delivery efficiencies of nebulizers for different breathing patterns

Abstract: Background Nebulizers are medical devices that deliver aerosolized medication directly to lungs to treat a variety of respiratory diseases. However, breathing patterns, respiration rates, airway diameters, and amounts of drugs delivered by nebulizers may be respiratory disease dependent. Method In this study, we developed a respiratory simulator consisting of an airway model, an artificial lung, a flow sensor, and an aerosol collecting filter. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…This means that during a stay in a mine/health resort, 58 to 70% of the inhaled PM is deposited in the respiratory tract during one respiratory cycle. According to Newman’s research, saline inhalations with the use of nebulisers result in the deposition of 10–40% of the inhaled substance (physiological saline solution of 0.9% NaCl) in the lungs, and the effectiveness of inhalation depends, among others, on skills, mask tightness and equipment efficiency [ 64 , 65 ]. The literature review proves that the studies described in this publication are one of the first studies on PM deposition in the respiratory tract of people receiving therapy in mine chambers, therefore the authors compared the obtained results to the results of studies carried out in indoor sports rooms, where a similar deposition model was used [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…This means that during a stay in a mine/health resort, 58 to 70% of the inhaled PM is deposited in the respiratory tract during one respiratory cycle. According to Newman’s research, saline inhalations with the use of nebulisers result in the deposition of 10–40% of the inhaled substance (physiological saline solution of 0.9% NaCl) in the lungs, and the effectiveness of inhalation depends, among others, on skills, mask tightness and equipment efficiency [ 64 , 65 ]. The literature review proves that the studies described in this publication are one of the first studies on PM deposition in the respiratory tract of people receiving therapy in mine chambers, therefore the authors compared the obtained results to the results of studies carried out in indoor sports rooms, where a similar deposition model was used [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to get around issues with jet nebulizers high production rates and irregular mass distribution, mesh nebulizers were created. They can be divided into passive (static) mesh nebulizers, and active (vibrating) mesh nebulizers, in which the mesh is set on a piezoelectric ring that vibrates [ 239 ]. Recent investigations have demonstrated that human adipose-derived mesenchymal stromal cells (MSC-EVs) can be nebulized using vibrating mesh [ 240 ], and ultrasonic nebulized hypoxic human umbilical cord MSC-EVs [ 241 ] create promising clinical applications in lung injury diseases.…”
Section: Pulmonary Drug Deliverymentioning
confidence: 99%
“…The residual volumes were obtained by measuring the weight of nebulizer before and after nebulization using an analytical balance. Output rates (mL/min) were calculated using the following formula [20]:…”
Section: Nebulization Performance and Drug Delivery E Ciency Evaluationmentioning
confidence: 99%